2012
DOI: 10.1590/s0102-05362012000300018
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização agronômica e pungência em pimenta de cheiro

Abstract: Nove acessos de Capsicum chinense do Banco Ativo de Germoplasma de pimentas do Instituto Agronômico (IAC) foram caracterizados e avaliados nas condições edafoclimáticas de Campinas (SP). O experimento foi realizado de janeiro a outubro de 2010, em blocos casualizados, com nove tratamentos, cinco repetições e oito plantas por parcela. Foram avaliados altura da planta, hábito de crescimento da planta, antese da primeira flor, produtividade, massa fresca do fruto, comprimento do fruto, largura do fruto, conteúdo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
4
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 14 publications
(1 reference statement)
0
23
4
13
Order By: Relevance
“…Results obtained in this for the CV were more favorable than those obtained in other studies with pepper (BENTO et al, 2007;NEITZKE et al, 2010;DOMENICO et al, 2012), which evidences a great genetic variability of the genotypes studied.…”
Section: Resultscontrasting
confidence: 45%
See 2 more Smart Citations
“…Results obtained in this for the CV were more favorable than those obtained in other studies with pepper (BENTO et al, 2007;NEITZKE et al, 2010;DOMENICO et al, 2012), which evidences a great genetic variability of the genotypes studied.…”
Section: Resultscontrasting
confidence: 45%
“…DOMENICO et al (2012), working with nine accessions of C. chinense, verified that length of the fruit (24.2%) and productivity (23.8%) were the characters that most contributed to the genetic divergence. SILVA NETO et al (2014), when characterizing a population of C. annuum, observed that diameter of the stem (68.97%) and diameter of the cup (9.22%) were the characteristics that contributed most.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Domenico et al (2012) The authors concluded that pruning management did not influence the growth and the production of BRS Mari. The use of pruning resulted in fruits with greater pungency and higher industrial quality.…”
Section: Resultsmentioning
confidence: 98%
“…Despite the importance of these fruits, statistical information on production and commercialization of pepper in Brazil are scarce and the available data do not show the real economic situation, since large part of the production is commercialized in local markets and this commercialization is not part of the statistics (Domenico et al, 2012).…”
Section: Resultsmentioning
confidence: 99%